Genetic and Biological Effects of SLC12A3, a Sodium-Chloride Cotransporter, in Gitelman Syndrome and Diabetic Kidney Disease - Li, Nan; Gu, Harvest F. (Frontiers in Genetics, 2022)
The SLC12A3 (Solute carrier family 12 member 3) gene encodes a sodium-chloride cotransporter and mediates Na+ and Cl- reabsorption in the distal convoluted tubule of kidneys. An experimental study has previously showed that with knockdown of zebrafish ortholog, slc12a3 led to structural abnormality of kidney pronephric distal duct at 1-cell stage, suggesting that SLC12A3 may have genetic effects in renal disorders. Many clinical reports have demonstrated that the function-loss mutations in the SLC12A3 gene, mainly including Thr60Met, Asp486Asn, Gly741Arg, Leu859Pro, Arg861Cys, Arg913Gln, Arg928Cys and Cys994Tyr, play the pathogenic effects in Gitelman syndrome. This kidney disease is inherited as an autosomal recessive trait. In addition, several population genetic association studies have indicated that the single nucleotide variant Arg913Gln in the SLC12A3 gene is associated with diabetic kidney disease in type 2 diabetes subjects. In this review, we first summarized bioinformatics of the SLC12A3 gene and its genetic variation. We then described the different genetic and biological effects of SLC12A3 in Gitelman syndrome and diabetic kidney disease. We also discussed about further genetic and biological analyses of SLC12A3 as pharmacokinetic targets of diuretics.